Thomas A. Jenckes papers - Jenckes, Thomas A. (Thomas Allen), 1818-1875.
Correspondence, diaries, journals, patent papers, legal briefs, ledgers, account books, law library catalog, photographs, and other papers pertaining chiefly to Jenckes's political and legal career in Rhode Island and the U.S. House of Representatives. Includes material pertaining to his patent law practice; service as Rhode Island state legislator, adjutant general, and secretary to the 1842 Constitutional Convention and to the governor's council; and student years at Brown University. Subjects include civil service reform; bankruptcy, patent, and copyright laws; the Credit Mobilier of America fraud prosecution; and patent cases involving the Corliss Steam Engine Company, Goodyear Tire and Rubber Company, and ventilation and refrigeration patents.
Correspondents include Benjamin Vaughan Abbott, Charles Adams, Henry B. Anthony, Hugh Burgess, Alexis Caswell, Horace H. Day, Ezra D. Fogg, George Gifford, B. Benton Hammond, Alexander Hay, J.E. Hilgard, Charles R. Ingersoll, David Lyman, Dennis F. Murphy, Francis C. Nye, James H. Parsons, William Sprague, Charles C. Van Zandt, Henry E. Wallace, and Augustus Woodbury.
Jurist, Rhode Island state legislator and adjutant general, and U.S. representative from Rhode Island.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbott, Benjamin Vaughan, -- 1830-1890 -- Correspondence; Adams, Charles, -- 1845-1895 -- Correspondence; Anthony, Henry B. -- 1815-1884 -- Correspondence; Burgess, Hugh -- Correspondence; Caswell, Alexis, -- 1799-1877 -- Correspondence; Day, Horace H., -- 1813-1878 -- Correspondence; Fogg, Ezra D. -- Correspondence; Gifford, George, -- 1811-1883 -- Correspondence; Hammond, B. Benton -- Correspondence; Hay, Alexander -- Correspondence; Hilgard, J. E. -- 1825-1891 -- Correspondence; Ingersoll, Charles R. -- Correspondence; Lyman, David -- Correspondence; Murphy, Dennis F. -- Correspondence; Nye, Francis C. -- Correspondence; Parsons, James H. -- Correspondence; Sprague, William, -- 1830-1915 -- Correspondence; Van Zandt, Charles C. -- 1830-1894 -- Correspondence; Wallace, Henry E. -- 1814-1879 -- Correspondence; Woodbury, Augustus, -- 1825-1895 -- Correspondence; Rhode Island. -- Constitutional Convention -- (1842); Rhode Island; Brown University -- Students; Corliss Steam Engine Company; Credit Mobilier of America; Goodyear Tire and Rubber Company; Bankruptcy; Civil service reform; Copyright; Fraud; Patent laws and legislation; Patents; Practice of law -- Rhode Island; Refrigeration and refrigerating machinery; Ventilation; Rhode Island -- Politics and government; United States -- Politics and government -- 1849-1877.; Jurists; Legislators -- Maryland; Public officials -- Rhode Island; Representatives, U.S. Congress -- Rhode Island